Penilaian Berbasis Kelas pada Pembelajaran Pendidikan Agama Islam di Madrasah - Hasan Baharun (MODELING: Jurnal Program Studi PGMI, 2016)
In learning activities, evaluation is an important component that must be taken by the teacher to know efektifias learning that has been done. The importance of evaluation in the classroom learning system aims to determine the various issues related to the development, progress, setbacks of a study, to be followed up as a learning-oriented development measures to improve the quality of learning in the classroom. In addition, the results obtained from the evaluation can be used as feedback for teachers in improving and learning activities.In this case, the evaluation or assessment should be viewed as one of the important factors that can give an idea to the teacher about the condition of learning activities they have implemented. These activities continue to be carried out so as to provide information to teachers on learning activities, both in terms of process and output of activities that have been carried out.